2014
DOI: 10.1002/fsn3.189
|View full text |Cite
|
Sign up to set email alerts
|

Plant extract enhances the viability of Lactobacillus delbrueckii subsp. bulgaricus and Lactobacillus acidophilus in probiotic nonfat yogurt

Abstract: A commercial plant extract (prepared from olive, garlic, onion and citrus extracts with sodium acetate (SA) as a carrier) was evaluated to extend the viability of yogurt starter and probiotic bacteria as a means to enhance the shelf life of live and active culture, probiotic nonfat yogurt. Yogurts prepared from three different formulas (0.5* plant extract, 0.25* SA, or no supplement) and cultures (yogurt starter plus Bifidobacterium animalis,Lactobacillus acidophilus, or both probiotics) were assessed weekly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
3
25
0
1
Order By: Relevance
“…Increases in E h and the hydrogen peroxide concentration coming from the metabolic activity of bacteria can lead to a reduction in bacterial counts during storage (Dave and Shah, 1997). Michael et al (2015) reported similar results when investigating the effect of adding herbal extract on the viability of Lactobacillus delbrueckii ssp. bulgaricus and Lactobacillus acidophilus in probiotic non-fat yogurt.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Increases in E h and the hydrogen peroxide concentration coming from the metabolic activity of bacteria can lead to a reduction in bacterial counts during storage (Dave and Shah, 1997). Michael et al (2015) reported similar results when investigating the effect of adding herbal extract on the viability of Lactobacillus delbrueckii ssp. bulgaricus and Lactobacillus acidophilus in probiotic non-fat yogurt.…”
Section: Discussionsupporting
confidence: 64%
“…The reason for this is the fact that milk fermentation with the herbal extracts increased the metabolic activity of the yoghurt bacteria, thus elevating the yoghurt acidity due to the production of organic acids by lactic acid bacteria (Amirdivani and Baba, 2011). Furthermore, the acidity of all samples increased significantly during storage (p < 0.05), because as the storage time increased, the lactose fermentation by the starter and probiotic bacteria proceeded, and acidity increased due to the accumulation of organic acids such as lactic acid and formic acid (Michael et al, 2015). Joung et al (2016) obtained similar results.…”
Section: Aciditymentioning
confidence: 86%
“…To our surprise, yogurt turned out to be relatively efficient in protecting phage from stomach juice, despite that in the case of milk no clear effect was observed. This may be associated with mildly acidic pH of Danone natural yogurt (5.29 according to Çaglar et al, 2011) and with the yogurt buffering activity (Kargul et al, 2007). In in vivo studies, the ingestion of yogurt was shown to stabilize the gastric pH for 1 h at the level exceeding 3.5 (Martini et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…After 28 days of storage, L. bulgaricus and L. acidophilus counts were greater compared to the non-supplemented yoghurts. Streptococcus thermophilus and Bifidobacterium animalis counts were not affected by supplementation.[88] Lactobacillus acidophilus Lactobacillus bulgaricus Streptococcus thermophilus Bifidobacterium lactis Bb-1272 children commenced and 70 children (36 placebo and 34 probiotic) completed the trial. There were no incidents of severe diarrhoea (stool consistency ≥6, ≥3 stools/day for ≥2 consecutive days) in the probiotic group and six in the placebo group (Fisher’s exact p = 0.025).…”
Section: Probiotic Lab and Yoghurt Starter Culturesmentioning
confidence: 99%